Characteristic region based image steganography using Speeded-Up Robust Features technique - Nagham, Hamid; Abid, Yahya; R. Badlishah, Ahmad, Prof. Dr.; Osamah Al-Qershi (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/